Intergenerational Equity and Transitional Inequality Measurement: Techniques and Empirics - Bova, Demetrio Miloslavo (European Journal of Sustainable Development, 2020)
This paper discusses the measurement of both the intergenerational equity and the transitional inequality where the latter is a measure of distance to a transitional goal. The issue is relevant especially for ecological sustainability which is the main aspect treated, and can be extended to a set of transitional goals as the Agenda 2030. The empirics show that we had non-sustainable intergenerational equity and that no transition has been performed; therefore, it is hard to believe that there will be no necessity for inequality to reach the intergenerational equity